The Effect of Work-Family Conflict on Job Satisfaction and Employee Performance - Kadek Iin Dwijayanti; I Gede Riana (Journal of Multidisciplinary Academic, 2018)
Stress is a condition in the workplace can be affect job satisfaction and employee performance. The aims of this research to analysis the effect of job stress on job satisfaction job stress on employee performance, and job satisfaction on employee performance. In this study, the observation data taken from 46 employees by using sampling technique. The descriptive and inferential analysis with partial least square (PLS) to test the hypotheses is used to obtain result. The result of the research shows that job stress has negative and significant effect on job satisfaction, job stress has negative and significant effect on employee performance, and job satisfaction has negative significant effect on employee performance. Furthermore, Job satisfaction cannot mediate relationship between job stresses on employee performance.